Otimização dos protocolos pediátricos de crânio: tomografia computadorizada em hospital universitário de grande porte - Bonfleur, Debora Regina (2022)
Computed tomography (CT) is a diagnostic imaging method with high doses of ionizing radiation delivered to the patient. In the case of pediatric patients, the concern with radiation doses is greater, due to the long-life expectancy and the fact that they are more radiosensitive than adults. Therefore, it was decided to carry out the study with pediatric patients, aged 0 to 12 years, subdivided into protocols from 0 to 2 years, 3 to 5 years and 6 to 12 years, all of whom underwent CT scans of skull. The objective of this work is to present a process of optimization of pediatric cranial CT protocols, for the mentioned age groups, evaluating image acquisition parameters and dose reduction, without loss of image quality. The CTDIvol and DLP index were verified in fifteen samples of each skull exam protocol, as well as image acquisition parameters. From these data, experimental protocols were developed, and the contrast-noise ratios of the images produced were analyzed and the figure of merit (FOM) was used as a quality metric to analyze the quality in comparison with the levels of CTDIvol and DLP. It was concluded that, although the dose index in the current protocols is consistent with the recommendation of international legislation, it was possible to reduce the CTDIvol and DLP index, in the three protocols studied – that is, a reduction of CTDIvol of 10.5% in the protocol from 0 to 2 years, 33% in the protocol from 3 to 6 years, and 16% in the protocols from 6 to 12 years. The DLP was reduced by 14%, 41% and 25%, respectively, for the 3 age groups, in relation to the protocols previously used. Regarding the FOM, there was an increase in quality, according to the FOM, of 6%, 19%, 43%, respectively, for the three age groups.